Tetti giardino: una proposta per Londra alla fine dell’Ottocento - Corsani, Gabriele (Ri-Vista. Research for landscape architecture, 2017)
The Nineteenth century proposals on growth control and for the renewal of London, defined as the New Babylon, ascribe to greenery a primary role. Benjamin Ward Richardson, in his essay Upper and Under London in The Common-health. A series of essays on health and felicity for every-day readers (1887), aims to transform the roofs of the metropolis into an aerial garden. Richardson, outstanding hygienist, reformer and prolific populariser, is closely interested in urban health and imagines a renewed London, achieved through the construction of roof gardens, or garden terraces, above every house, each of them connected to each other through a network of bridges allowing access to everyone. The hygienic advantages are united to a very suggestive result in terms of landscape. Alfred Richard Sennett, in his treatise Garden Cities in theory and practice (1905), refers to that proposal and illustrates it with four photographic images.